(untitled) (Research, Society and Development, 2020)
In the search for an approximation between Statistical Education and Early Childhood Education, we aim to: 1) identify articles published in editions of scientific events in the area of ​​Mathematics Education to characterize practices to be developed (2013-2017); and 2) to establish points of articulation of the theme investigated from the perception of Professor Celi Espasandin Lopes, a reference in Brazil when the subject is Stochastic in childhood. The methodology fits in the qualitative studies in which a questionnaire with open questions to the researcher was used. In conclusion, we identified: a) few theoretical and methodological references to guide the teacher on the notions of Statistics and Probability with the child; and b) the need for studies/research, in interventional experiences, to assist teachers and future teachers to work with these concepts.